Kelayakan Aksesoris Rambut Dengan Bahan Dasar Kulit Bawang Putih (Allium Sativum) (Department of Home Economics, Faculty of Engineering, Universitas Negeri Semarang, 2023)
Abstract. Garlic peel is only considered as garbage, processing garlic peel is only used for herbal medicine ingredients, a mixture of organic fertilizers and handicrafts such as wall hangings and table decorations. Researchers took the initiative to use garlic skin as hair accessories. The purpose of the study was to determine the feasibility of garlic skin as a basic material for making hair accessories using sensory tests and preference tests. This type of research is experimental. The research object is 3 hair accessories. The validity of the instrument using expert judgment includes 3 Lecturers of the Department of Family Welfare Education. The research subjects were 3 expert panelists for product validity including Beauty Assessor LSP ESCRINS, Accessories shop owner Valerian Artisan, and Art Director Lie Kuang Salon, 3 expert panelists for sensory testing including DPC Chairman Tiara Kusuma Semarang Regency, Chairperson of Harpi Melati Branch Pringapus Karangjati, shop owner Sari Accessories and 20 respondents who own salons and make-up studios. Methods of data collection using observation and documentation. The data analysis method used descriptive percentage. The results of the product validity test were declared very valid with an average result of 94%. Sensory test results were declared very feasible with an average result of 94%. The results of the preference test by salons and make-up studios were stated to be very favorable with an average result of 89%. Conclusions (1) Hair accessories products made from garlic skin are declared